Using the 12-item General Health Questionnaire (GHQ-12) to assess the psychological health of Malaysian college students - Zulkefly, Nor Sheereen; Baharudin, Rozumah (Canadian Center of Science and Education, 2010)
The primary objective of this study was to assess the psychological health of students at a local university in Malaysia using General Health Questionnaire (GHQ-12). Additionally, the study was carried out to determine the reliability and factor structure of the GHQ-12. Sample comprised 386 students (female=177, male=209) who were selected using multistage cluster sampling. A self-administered questionnaire was used to collect the data required. Results showed that slightly more than half (52.9%) of the respondents scored low on the GHQ-12, and a substantial proportion (47.1%) of them scored high, indicating an unhealthy psychological state. Nevertheless, no differences were observed between the genders. Reliability analysis showed satisfactory results, with a Cronbach’s alpha of 0.70. Meanwhile, factor analysis revealed that GHQ-12 was a measure of psychological distress, with a three-factor structure (Psychological Distress, Social and Emotional Dysfunction and Cognitive Disorder), which jointly accounted for 51.9% of the variance. The findings of the study therefore affirm that the GHQ-12 is a good measure for assessing the overall psychological well-being of students in Malaysia.